Cultural parks as a tool for shaping and protecting public spaces in Cracow - Mol, Paulina (Protection of Cultural Heritage, 2023)
The Act of July 23, 2003 on the protection and care of historical monuments introduced into the Polish legal system a new form of monument protection in the form of cultural parks. The purpose of its establishment is to protect immovable monuments and the cultural landscape found in a certain area. For almost 20 years of operation of this form of monument protection, still few local governments have decided to establish cultural parks on the territory of a municipality (or several municipalities). Nevertheless, with clearly formulated provisions and consistent enforcement, cultural parks can be an effective tool for protecting and shaping the public spaces of Polish towns and villages. The above-mentioned topics are discussed in this article on the example of cultural parks operating in Krakow.